On Euler-Lagrange’s Equations: A New Approach - Giacaglia, G. E. O.; Lamas, W. Q. (Trends in Computational and Applied Mathematics, 2020)
A new formalism is proposed to study the dynamics of mechanical systems composed of N connected rigid bodies, by introducing the concept of 6N-dimensional composed vectors. The approach is based on previous works by the authors where a complete formalism was developed by means of differential geometry, linear algebra, and dynamical systems usual concepts. This new formalism is a method for the description of mechanical systems as a whole and not as each separate part. Euler-Lagrange’s Equations are easily obtained by means of this formalism.